Discovery of 4-(4-aminopyrazolo[1, 5-a][1, 3, 5]triazin-8-yl)benzamides as novel, highly potent and selective, orally bioavailable inhibitors of Tyrosine Threonine Kinase, TTK. Issue 15 (1st August 2016) - Laufer, Radoslaw; Li, Sze-Wan; Liu, Yong; Ng, Grace; Lang, Yunhui; Feher, Miklos; Brokx, Richard; Beletskaya, Irina; Hodgson, Richard; Mao, Guodong; Plotnikova, Olga; Awrey, Donald E.; et al.
Graphical abstract: Abstract: TTK/Mps1 is a key kinase controlling progression of cell division via participation in the mitotic spindle assembly checkpoint and is overexpressed in a number of human cancers. Herein we report the discovery of 4-(4-aminopyrazolo[1, 5- a ][1, 3, 5]triazin-8-yl)benzamides as a potent, novel class of TTK inhibitors. The series was identified by means of bioisosteric replacement of the related imidazopyrazine and imidazopyridazine scaffolds. Optimization led to the identification of compounds with excellent potency ( K i  = 0.8 nM) and exceptional kinase selectivity. The SAR indicates a strong dependence of activity on the presence of the N -cyclopropyl-2-methylbenzamide moiety delineating the geometry for 1½ type kinase inhibitor. Molecular modeling indicates the extensive and optimal contacts, mediated through H-bonds and hydrophobic interactions, are responsible for the selectivity and potency of the inhibitors. The compounds demonstrate a strong anti-proliferative activity in a panel of human cancer cell lines (HCT116 GI50  <15 nM) and good rodent pharmacokinetics (oral %F 97%).